Risk factors of cardiovascular diseases in young and middle aged Indian males: a case control study - Singh, Harpreet; Kaur, Kanwaljit; Gangwar, Surjit Singh; Katoch, Shilpa; Patel, Barun Bhai; Nayak, Rahul (International Journal Of Community Medicine And Public Health, 2023)
Background: Cardiovascular diseases (CVDs) are common in India, yet there is a lack of comprehensive studies on the specific risk factors for the Indian population. Our research aimed to identify CVD risk factors in individuals under 50 and compare them with healthy controls, offering insights into preventing CVDs in this younger demographic. Methods: This study focused on newly diagnosed cases of CVDs in males under 50 and matched controls with same demographic parameters. Data on personal, medical, lifestyle and biochemical parameters was compared to identify and understand the key risk factors associated with CVDs in this specific population group. Results: Elevated body mass index (BMI) and waist-hip ratio were linked to CVD, with BMI showing a significant association. High triglyceride (TGL) levels (>150 mg/dl) and LDL cholesterol levels (>130 mg/dl) were significantly associated with CVD. The total cholesterol to HDL cholesterol ratio (>4.5) and low HDL cholesterol (<40 mg/dl) were also linked to CVD risk. Diabetes mellitus was strongly associated with CVD (OR-14.04). Stress, as assessed by a stress score >12, was associated with CVD, although the association was not very strong (OR 1.39). Physical exercise was associated with a protective effect against CVD (OR-0.28). These findings emphasize the critical role of lifestyle factors, such as diet, exercise and stress management in CVD prevention and highlight the importance of managing conditions like obesity and diabetes. Conclusions: This study not only deepens our comprehension of CVD prevention but also provides actionable guidance for fostering heart health, both within the studied population and in broader contexts.